Smash Skills In Table Tennis Games - Nasution, Usman; Ahady, Muhammad Yan; Pratiwi, Vivi; Albanjari, Fatimah Zahrah; Tarigan, Elvita Sari Br; Siregar, Xyena Tesalonika Br (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The game of table tennis is a popular sport and is well known by almost all levels of Indonesian society, both in cities and villages, from children to the elderly. The aim of this research is to produce a product in the form of a smash skill instrument in table tennis games, as well as to obtain the validity and reliability of the smash skill instrument in table tennis games. This research uses the research and development (RD) method.